Abdurrahman Wahid's Policy Motivation for the Cheng-ho Mosque (Multicultural Da'wah Communication Perspective) - Husnan, Moch; Zuhriyah, Luluk Fikri (Jurnal Multidisiplin Madani, 2023)
This research aims to find a motive that underlies Abdurrahman Wahid's approach to the Cheng-ho Mosque in the context of multicultural da'wah. Cheng-ho Mosque, is a mosque that is quite often located in Indonesia. This mosque attracts attention because of its unique combination of architecture and cultural diversity. The focus of this research is to understand the motivation behind Abdurrahman Wahid's support for this mosque, and how this is reflected in his multicultural da'wah approach. The research method used is qualitative with a literature analysis and literature study approach. Primary data is collected through books, articles, newspapers, historical records, journals, encyclopedias and digital archives to collect data directly related to the figure. Secondary data is obtained from reviewing existing literature by examining previous research on the same subject or figure. Carrying out this literature review can help avoid repeating research that has been done previously and help have in-depth knowledge of Abdurrahman Wahid's thoughts and views on the Cheng-ho mosque. The research results show that Abdurrahman Wahid's motives for the Cheng-ho Mosque are rooted in his beliefs and multicultural approach in spreading Islamic teachings. He views this mosque as a symbol of cultural diversity that can become a bridge to strengthen relations between Muslims and non-Muslim communities in Indonesia. Abdurrahman Wahid sees the potential of the Cheng-ho mosque as a place for interfaith dialogue, spreading the values of tolerance, and developing social harmony. From a multicultural da'wah perspective, Abdurrahman Wahid's approach to the Cheng-ho mosque emphasizes the importance of inclusion and mutual understanding between religious communities. He promotes Islamic teachings that are able to respect cultural diversity and emphasize the values of brotherhood between religious communities. By using the Cheng-ho mosque as a means of da'wah, Abdurrahman Wahid is trying to change the paradigm of preaching from a more exclusive to an inclusive one, so that he can build a more harmonious societ